The Effect of Financial Literacy and Perception of Convenience on QRIS Usage Decisions in Gen Z of Surabaya - Khulilurrohman, Muhammad; Kusumasari, Indah Respati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of financial literacy and the perception of convenience on the decision to use QRIS in Generation Z in the city of Surabaya. QRIS (Quick Response Code Indonesian Standard) is a digital payment system innovation that is expected to encourage financial inclusion and transaction efficiency. This study uses a quantitative approach with a survey method, where data is collected through questionnaires from 100 respondents who are part of Generation Z in Surabaya. The data were analyzed using validity, reliability, classical assumption test, multiple linear regression, t-test, and F-test. These findings reinforce the important role of financial education and the ease of technology in driving the adoption of digital payment systems among the younger generation. This research is expected to contribute to the development of promotion and education strategies by the government and digital financial service providers.